Labor force dynamics and economic performance: A case of Nigeria, India, and China - Oyedepo Elizabeth Omolola (Journal of Economics and Management)
Aim/purpose – This study investigated the nexus between labor force dynamics and economic performance in Nigeria, India, and China.